Characterization of effector cells of graft vs leukemia following allogeneic bone marrow transplantation in mice inoculated with murine B-cell leukemia. - Weiss, L; Weigensberg, M; Morecki, S; Bar, S; Cobbold, S; Waldmann, H; Slavin, S (Springer-Verlag, 1990)
It is now widely accepted that immunocompetent lymphocytes in allogeneic bone marrow grafts exert an antileukemic effect that contributes to the cure of leukemia. Graft vs leukemia (GVL) effects independent of graft vs host disease were investigated in allogeneic bone marrow chimeras tolerant of host and donor alloantigens. The role of Thy1.2, L3T4 and Lyt2 T lymphocytes as effector cells of GVL were investigated in (BALB/c x C57BL/6)F1 mice inoculated with murine B-cell leukemia and subsequently conditioned with total lymphoid irradiation and cyclophosphamide (200 mg/kg). Mice were reconstituted with C57BL/6 bone marrow cells depleted of well-defined T-cell subsets or enriched for stem cells by the soybean agglutination method. Detection of residual tumor cells, an indicator for efficacy of GVL, was carried out by adoptive transfer of peripheral blood or spleen cells obtained from treated chimeras into secondary naive BALB/c recipients at different time intervals following bone marrow transplantation. Treatment of the primary marrow inoculum with monoclonal anti-Thy1.2 or anti-Lyt2 abolished the GVL effects and all secondary BALB/c recipients developed leukemia within 60 days. On the other hand, the treatment with monoclonal anti-L3T4 did not influence the effect of GVL and all treated recipients remained without leukemia. The data suggest that T cells may mediate GVL effects in the absence of graft vs host disease and in circumstances where tolerance to conventional alloantigens is elicited. Effector cells of GVL across the major histocompatibility complex (MHC) in the murine B-cell leukemia tumor model system appear to be Thy1.2+ Lyt2+ L3T4-. Induction of GVL effects by allogeneic cells tolerant of host MHC suggests that these effects may be independent of graft vs host disease.